2016
DOI: 10.5665/sleep.5856
|View full text |Cite
|
Sign up to set email alerts
|

Individual Differences in Animal Stress Models: Considering Resilience, Vulnerability, and the Amygdala in Mediating the Effects of Stress and Conditioned Fear on Sleep

Abstract: Outbred Wistar rats can show significant individual differences in the effects of stress on REM that are mediated by BLA. These differences in REM can be independent of behavioral fear and the peripheral stress response, and may be an important biomarker of stress resilience and vulnerability.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

9
55
0
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
3
3

Relationship

1
5

Authors

Journals

citations
Cited by 31 publications
(65 citation statements)
references
References 96 publications
9
55
0
1
Order By: Relevance
“…As with previous studies, [8][9][10] we found that contextual reexposure alone could alter REM. ANOVA revealed a Group × Treatment interaction (F 1, 14 = 5.68, p < .04) for comparisons of Baseline and CTX1 for total 20-h REM.…”
Section: Nphr-mediated Peri-shock Inhibition Of Bla Significantly Incsupporting
confidence: 90%
See 4 more Smart Citations
“…As with previous studies, [8][9][10] we found that contextual reexposure alone could alter REM. ANOVA revealed a Group × Treatment interaction (F 1, 14 = 5.68, p < .04) for comparisons of Baseline and CTX1 for total 20-h REM.…”
Section: Nphr-mediated Peri-shock Inhibition Of Bla Significantly Incsupporting
confidence: 90%
“…This is most apparent in training with inescapable footshock (IS; an uncontrollable stressor) which can reduce subsequent REM, whereas training with escapable footshock (ES) or avoidable footshock (controllable stressors) can be followed by increases in REM. [8][9][10] Indices of stress, such as stress-induced hyperthermia (SIH), 11 and fear memory, such as behavioral freezing, 12 can be virtually identical in situations that produce increases or decreases in REM. 10,13 Outbred rats can show significant variations in poststress REM after very similar stressors, thereby suggesting that individual differences in stress responsivity are also involved in mediating the effects of stress on sleep.…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations